Konsep Pendidikan Akhlak Menurut Syekh Al-Zarnuji Dalam Kitab Ta'lim Al-Muta'allim - Abdul Qahar Zainal; Ansar Ansar (Education and Learning Journal, 2021)
This study discusses the concept of moral education according to Sheikh Al-Zarnuji in the book of Ta'lim Al-Muta'allim. This research is focused on analyzing the concept of moral education according to Sheikh Al-Zarnuji in the Book of Ta'lim Al-Muta'allim. Data analysis used the descriptive qualitative method. The researcher's main research instrument is the researcher himself, who identifies, classifies, and analyzes data from any data needed to complete the research. The findings reveal that the book of Ta'lim Al-Muta'allim has 13 significant conversations, including the essence of science, the law of pursuing knowledge, and its significance. Set a goal to learn something new; choose ability, teachers, friends, and learning perseverance; About how to respect science and teachers; about honesty in pursuing understanding, noble and noble character, and values; and how to respect science and teachers. Concerning the beginning of education, its scope, and discipline, Tawakkal and surrender to God are two words that come to mind when I think of Tawakkal. Concerning the study period; Concerning loving and guiding one another; Concerning the study period; Concerning the study period; Concerning the study period; Take knowledge for example; The current state of study; Things that can both increase and weaken memorization; Things that make it easier to bring good fortune, prolong life, and save energy are all good things. Regarding moral education itself, three broad lines form the foundation of moral education: the Value of Moral Education to Allah SWT; The Value of Moral Education Towards Themselves; and moral education towards fellow creatures.